Substituted pyrrole synthesis from nitrodienes. Issue 23 (7th June 2017) - Karimi, Sasan; Ma, Shuai; Liu, Yanan; Ramig, Keith; Greer, Edyta M.; Kwon, Kitae; Berkowitz, William F.; Subramaniam, Gopal
Graphical abstract: Highlights: A general method to make pyrroles from nitrodienes, in one step, is reported. The yield of cyclization is increased with the use of Mo catalyst. DFT calculations supports a reaction path through a nitrene intermediate. Abstract: Though the Cadogan-Sundberg approach has been employed to synthesize a variety of indole and carbazole derivatives from nitroarenes, surprisingly, very little is reported for making pyrroles using the same approach from non-arene nitrodienes. Herein, we report a general method to synthesize substituted pyrroles, in one step with modest yields, from nitrodienes using triphenylphosphine in the presence of an Mo catalyst, bis(acetylaceto)dioxomolybdenum (VI). To shed light on the mechanism of this reaction, we performed DFT calculations using uB3LYP/6-31+G(d) basis set and observed that the reaction favors a path through a nitrene intermediate.